Fairness in winner-take-all competitions - Björn Bartling; Alexander W. Cappelen; Mathias Ekström; Erik Ø. Sørensen; Bertil Tungodden (University of Zurich, Department of Economics, 2024)
Negative externalities, social and environmental responsibility, income effects, market experimentsThis paper reports the results of a large-scale incentivized experiment investigating individuals' fairness perceptions of the extreme income inequalities generated in winner-take-all competitions. We find that extreme income inequality in winner-take-all competitions is commonly accepted in our sample of 4,000 participants from the general population of the U.S., even when the winner outperforms the runner-up by the smallest possible margin. Generally, fairness judgements are only weakly influenced by the winning margin, which reveals that the mere fact of winning-be it by a tiny margin or by a substantial gap-justifies resulting inequalities. Our results improve understanding of public attitudes toward fairness and redistributive policies in winner-take-all competitions marked by extreme income inequalities.
Keywords: C91; D31; D63; 330; Winner-take-all competitions; winning margin; merit; fairness; income inequality; redistributive policies